2022
DOI: 10.3390/biom12030348
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Epithelial-Mesenchymal Heterogeneity in Cancer Cells

Abstract: Phenotypic heterogeneity is a hallmark of aggressive cancer behaviour and a clinical challenge. Despite much characterisation of this heterogeneity at a multi-omics level in many cancers, we have a limited understanding of how this heterogeneity emerges spontaneously in an isogenic cell population. Some longitudinal observations of dynamics in epithelial-mesenchymal heterogeneity, a canonical example of phenotypic heterogeneity, have offered us opportunities to quantify the rates of phenotypic switching that m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The degree of resolution among distinct cell-states depends on the number of biomarkers used experimentally to identify a cell population [5,6,18,44,45]. These cell-states can transition between each other either spontaneously due to factors such as stochastic gene expression and asymmetric cell division, or under microenvironmental influence such as TGFβ signalling and altered matrix stiffness [28,39,[46][47][48]. Recently, frequency of spontaneous cell-state transition has been shown to depend on the mRNA and protein half-life.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of resolution among distinct cell-states depends on the number of biomarkers used experimentally to identify a cell population [5,6,18,44,45]. These cell-states can transition between each other either spontaneously due to factors such as stochastic gene expression and asymmetric cell division, or under microenvironmental influence such as TGFβ signalling and altered matrix stiffness [28,39,[46][47][48]. Recently, frequency of spontaneous cell-state transition has been shown to depend on the mRNA and protein half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach, while useful for robustly characterizing EMT at the single-cell level, is not without limitation. Phenotypically heterogeneous cells can exhibit gene expression profiles that cooperate or interfere with overall signal detection 1 , and this is further compounded by noisy celular division 21 . Although we have assumed in our analysis that populations under study were non-dividing, cell cycle scoring suggested the variable presence of division signatures across available experimental contexts as shown in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, not all cells are responsive to the EMT-inducing signal resulting 75 in considerable phenotypic intra-tumoral heterogeneity and coexistence amongst multiple states 66 (Figure 1B). This has been reinforced by experimental observations supporting the existence of phenotypic transitions amongst EMT states as well as model-driven predictions of phenotypic heterogene-80 ity generated by noisy cell division 21,58 . Furthermore, the environmental cues that govern these cell state transitions are highly context-specific 43,62 .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The degree of resolution among distinct cell-states depends on the number of biomarkers used experimentally to identify a cell population (Bhatia et al, 2019a; Karacosta et al, 2019; Pastushenko et al, 2018; Pillai and Jolly, 2021; Ruscetti et al, 2016). These cell-states can transition between each other either spontaneously due to factors such as stochastic gene expression and asymmetric cell division, or under microenvironmental influence such as TGFβ signaling and altered matrix stiffness (Cook and Vanderhyden, 2020; Jain et al, 2022; Matte et al, 2019; Tripathi et al, 2020a; Zhao et al, 2021). The relative rates of cell-state transitions define the population distribution of cells along the E-M axis, as evident from dynamics of isolated subpopulations in vitro and in vivo (Bhatia et al, 2019b; Pastushenko et al, 2018; Yamamoto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%